Pelatihan dan Pendampingan Penyusunan Laporan Keuangan di Masjid Pondok Pesantren Al-I’tishom Kubu Raya - Prasetyo, Henri (Kapuas, 2022)
The news about the Kapal Munzalan Mosque Foundation, which was considered not transparent in the management of its funds by a community group, became hotter because representatives of the community group insisted that they be brought into the realm of law if financial reports were not provided. The implementation team imagined that this incident could happen to a large foundation in West Kalimantan with modern financial management, especially for mosque administrators whose reporting was still not good. Moving on from this, the implementation team is worried that they will be exposed to bad slander against the management of the Al I'tishom Islamic Boarding School Mosque which will only be established in 2021 with poor financial management. The implementation team identified the financial problems experienced by the Al I'tishom Islamic Boarding School Mosque using the fishbone method which resulted in 4 (problems), namely: low understanding of accounting from mosque administrators (Man Power), no standards used in compiling reports mosque finance (Materials), there is no financial management training for mosque administrators (Method), and there is no financial application used to compile mosque financial reports (Machine). The problem of Man Power, Method, and Material is given a solution by providing training and assistance in preparing financial reports according to financial accounting standards. For the problem (Machine), a solution is offered by presenting a financial application (Ai-Masjid). The output of the activities produced in this activity is the 2021 mosque financial reports and printed financial reports using the Ai-Masjid application. The positive response reached 100% from all mosque administrators at the Al-I'tishom Islamic Boarding School. With this activity, it is hoped that the negative views on the management of mosque funds can be overcome and regain public trust in mosques.